Hybrid polymer/porous silicon nanofibers for loading and sustained release of synthetic DNA-based responsive devices. Issue 4 (13th January 2020) - Zuidema, Jonathan M.; Bertucci, Alessandro; Kang, Jinyoung; Sailor, Michael J.; Ricci, Francesco
Abstract : Synthetic DNA-based oligonucleotides are loaded into porous silicon nanoparticles and incorporated into polymer nanofibers. The functionality of these input-responsive nanodevices is retained following release from the hybrid nanofibers. Abstract : Synthetic DNA-based oligonucleotides are loaded into porous silicon nanoparticles (pSiNPs) and incorporated into nanofibers of poly(lactide- co -glycolide) (PLGA), poly-l -lactic acid (PLA), or polycaprolactone (PCL). The resulting hybrid nanofibers are characterized for their ability to release the functional oligonucleotide payload under physiologic conditions. Under temperature and pH conditions mimicking physiological values, the PLGA-based nanofibers release >80% of their DNA cargo within 5 days, whereas the PLA and PCL-based fibers require 15 days to release >80% of their cargo. The quantity of DNA released scales with the quantity of DNA-loaded pSiNPs embedded in the nanofibers; mass loadings of between 2.4 and 9.1% (based on mass of DNA-pSiNP construct relative to mass of polymer composite) are investigated. When a responsive DNA-based nanodevice ( i.e. molecular beacon) is used as a payload, it retains its functionality during the release period, independent of the polymer used for the formation of the nanofibers.